JEP 2021
DOI: 10.7176/jep/12-27-14
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Affecting the Implementation of Teaching Practice: The Case of the University of Zambia

Abstract: For many years, the process of training a teacher has been extensively studied and discussed in the scientific and academic community worldwide. However, very few studies have been conducted on teaching practice in the developing world, which include Zambia. Teaching practice affords student teachers an opportunity to translate theory into practice in a real classroom situation. This study investigated challenges that the University of Zambia faces in implementing teaching practice in schools. In addition, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Using IA presents numerous challenges. The challenges that teachers and students face when using participatory methods which are attributed to the lack of teaching materials, are consistent with Luchembe [34] who claim that the environmental situation and the location of schools are the challenges that impede the effective use of interaction. Furthermore, the study conducted by Ayeni and Olowe [5] in Ghana found that the students were neither organized nor participating effectively in the relevant classroom activities as a large number of students exceeded the classroom capacity in most schools.…”
Section: Challenges Of the Interaction Approach (Ia)supporting
confidence: 66%
“…Using IA presents numerous challenges. The challenges that teachers and students face when using participatory methods which are attributed to the lack of teaching materials, are consistent with Luchembe [34] who claim that the environmental situation and the location of schools are the challenges that impede the effective use of interaction. Furthermore, the study conducted by Ayeni and Olowe [5] in Ghana found that the students were neither organized nor participating effectively in the relevant classroom activities as a large number of students exceeded the classroom capacity in most schools.…”
Section: Challenges Of the Interaction Approach (Ia)supporting
confidence: 66%
“…Conformability was further solidified through an external audit and was checked by seeking participants' feedback on findings and interpretations. In this research, ethical principles such as protecting participants' dignity and ensuring confidentiality were ensured by assigning symbols like PTs to report findings accurately (Luchembe, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Some schools of education are joined with other faculties, such that other faculties teach content. In contrast, schools of education handle the methodology and foundation course's parts during theory, while both entities are involved in field supervision (Luchembe, 2021).…”
Section: Stp In Malawi and Zambiamentioning
confidence: 99%
“…Field practicum duration and model vary with countries and institutions (Luchembe, 2021) due to policy, urgency, and human and nonhuman resource availability (Cuane, 2022; Tahir, 2003). Sometimes supervision coincides with campus theory work, which has a daunting impact on commissioning and the frequency of supervision (Sempowicz & Hudson, 2011).…”
Section: Introductionmentioning
confidence: 99%